The protection of traditional cultural expressions ? seeking international consensus for a multilateral solution - Harbs, Carolina (Department of Commercial Law, 2024)
Traditional Cultural Expressions (TCEs) as part of indigenous cultural heritage have been misappropriated and commercially exploited by western culture for centuries. Existing intellectual property laws, the closest conceptually related legal regimes, fail to protect TCEs because they were not developed with indigenous culture in mind. Despite over twenty years of negotiations at the Intergovernmental Committee on Intellectual Property and Genetic Resources (GR), Traditional Knowledge (TK), and Folklore at the World Intellectual Property Organisation (WIPO IGC), a binding agreement on an appropriate protection mechanism has yet to be found. Based on the novel hypothesis that the identification of a lowest common denominator forms the most realistic starting point for an agreement, the research question of this thesis asks where consensus exists between the most conflicting positions at the WIPO IGC and how this common ground can be leveraged to conceptualise a legal framework that will form a realistic base for an international agreement. This original approach focuses exclusively on TCEs and establishes a first-of-its-kind analysis of a multilateral law-making procedure. The methodological approach follows a three-part legal analysis. In the first stage, the current gaps in international law for the protection of TCEs are identified, and the consensus-finding and dispute-resolution mechanisms implemented at the WIPO IGC are evaluated. The second stage contains a legal doctrinal study of domestic approaches of specific parties and selected customary law. The third step contains an analysis and comparison of the different stakeholder positions regarding the draft law currently negotiated at the WIPO IGC. The study focuses on the United States of America, the European Union, South Africa, and the Indigenous Caucus, reflecting the parties whose positions are most at odds. The analyses yield that, should the current conditions persist, the WIPO IGC will not reach a binding agreement amongst all participating parties. Their approaches and positions are, in part, mutually exclusive, and the negotiation procedure at the IGC is no longer suited for parties with such diametrically opposed political and economic interests. To reach an agreement, the author of this thesis recommends specific changes to the wording of the draft law and the negotiation procedure. Procedurally, the tool of majority voting on pressing matters should be reintroduced, and the number of vetoes on matters of text-drafting should be limited. On a national level, governments should simultaneously draft domestic laws to protect TCEs and support indigenous communities through existing IP tools. Keywords: Traditional Cultural Expressions; Intellectual Property Law; Multilateral Dispute Resolution; Consensus-Finding; Traditional Knowledge; Intergovernmental Committee on Traditional Knowledge; Genetic Resources and Folklore; World Intellectual Property Organisation